Pengaruh MEDVIK (Media Edukasi Serviks) Terhadap Pengetahuan Wanita Usia Subur Tentang Deteksi Dini Kanker Serviks Dengan Metode IVA - Durratun Juita; Nur Cory'ah, Fitra Arsy; Intan Gumilang Pratiwi; Sundayani, Lina (Indonesian Health Issue, 2025)
Background: Cancer is one of the non-communicable diseases that has become a public health problem worldwide including in Indonesia. Based on GLOBOCAN 2018 data in the world there are 18.1 million new cases of cancer. In Indonesia, cervical cancer cases are very high. The number of new cases of cancer found in 2020 was 396,914 cases, as many as 9.2% (36,633) were cases of cervical cancer Preventive and promotive actions can be taken to improve health status through promotion and health education on early detection of cervical cancer using media, one of which is MEDVIK (Cervical Education Media). Purpose: To determine the effect of health counseling with MEDVIK on increasing the knowledge of women of childbearing age in efforts to early detect cervical cancer with the Iva method. Methods: This research is a quantitative research with Quasi Experiment method with pretest-posttest design. Sampling with purposive sampling technique as many as 108 respondents. Data analysis using the Mann Whitney test. Results: The mean knowledge value before intervention was 40.46, after intervention 82.69. The mean knowledge value before treatment in the control group was 36.30 and after treatment 63.06. The Mann Whitney analysis test with a P-Value of 0.000 < 0.05 shows a significant difference in the two groups. Conclusion: The use of MEDVIK has an effect compared to leaflets in increasing the knowledge of women of childbearing age about early detection of cervical cancer using the IVA method.